KEBUDAYAAN ISLAM SEBAGAI LITERASI PADA GENERASI MILENIAL - Rina Aditya Sartika; Nurbaiti (UIN Sunan Kalijaga, 2022)
The purpose of writing this scientific article is to describe the concept of the development of Islamic culture. In addition, this article also describes the concept of Islamic culture, the development of Islamic culture during the Khulafaur Rasyidin era, acculturation of Islamic culture in Indonesia, and the values ​​of Islamic culture. This article aims as literacy material, which is to increase knowledge and understanding of Islamic culture, especially for the milenial generation. The method used for reviewing this article is a literature study. The data obtained were compiled, analyzed, and conclsuded to obtain conclusions regarding the study of literature. The result is that the values ​​of Islamic culture and civilization are important in the life of the academic and intellectual community, the birth of Muslim intellectual thoughts needs to be encouraged with attitude; oriented to devotion and divine truth, think critically and innovatively, work hard, be open, honest, fair, responsible, sincere, and disciplined.